Fully biobased multiblock copolymers of furan-aromatic polyester and dimerized fatty acid: Synthesis and characterization. (2nd September 2016) - Kwiatkowska, Magdalena; Kowalczyk, Inez; Kwiatkowski, Konrad; Szymczyk, Anna; Rosłaniec, Zbigniew
Abstract: A series of poly(trimethylene 2, 5-furandicarboxylate – block – dimerized fatty acid) (PTF-b-FADD) copolymers was synthesized from 2, 5-furandicarboxylic acid (FDCA), 1, 3-propanediol (1, 3-PD) and dimerized fatty acid diol (FADD) via a polycondensation in melt. The copolymers were characterized in regard of their chemical structure, microstructure, thermal transitions, thermal stability, and mechanical performance. A detailed analysis of PTF-b-FADDs confirmed their multiblocked structure with randomly distributed rigid and flexible segments, while their microstructure indicated its heterogeneous nature with one continuous FADD/PTF blended phase, and the phase separation forced by the PTF crystalline domains. As the result the furan-aromatic copolyesters reveal the features of thermoplastic elastomers with the phase transition temperatures, thermal and mechanical properties governed by PTF to FADD ratio. All of the monomers used for copolymers' synthesis were plant-derived, what makes PTF- block -FADDs 100% bio-based polymeric materials. Graphical abstract: Highlights: Furan – aromatic polyester and dimerized fatty acid copolymers were synthesized. All monomers used for the synthesis were plant-derived. The PTF- block -FADDs reveal heterogeneous structure with micro-phase separation. Copolymers reveal features of thermoplastic elastomers govern by PTF/FADD ratio.